2020
DOI: 10.3389/fchem.2020.00216
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Preparation of Improved NiMo-Alumina Deoxygenation Catalysts

Abstract: This investigation deals with NiMo-alumina hydrotreating catalysts effective in the deoxygenation of rapeseed oil. The main goal was to compare catalyst structure and their deoxygenation performance and to link these parameters to reveal important structural information regarding the catalyst's intended use. Catalysts were prepared from different precursors (nickel acetate tetrahydrate/molybdenyl acetylacetonate in ethanol and water vs. nickel nitrate hexahydrate/ammonium heptamolybdate tetrahydrate in water),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In the case of NiMo/Al the X‐ray diffraction peaks of Ni (2θ=44.5° and 51.8°) [71] and Mo (2θ=40.5° and 50.7°) [72–74] species were not detected but small peaks of Ni at 2θ=44.5° and Mo at 2θ=40.5° were seen in the diffractogram of the fresh catalyst. γ‐Al 2 O 3 peaks of the fresh catalyst at 2θ=37.7°, 45.9° and 66.9° had a slightly higher intensity than those of the spent catalyst in which also the graphitic carbon peak was detected [70] .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of NiMo/Al the X‐ray diffraction peaks of Ni (2θ=44.5° and 51.8°) [71] and Mo (2θ=40.5° and 50.7°) [72–74] species were not detected but small peaks of Ni at 2θ=44.5° and Mo at 2θ=40.5° were seen in the diffractogram of the fresh catalyst. γ‐Al 2 O 3 peaks of the fresh catalyst at 2θ=37.7°, 45.9° and 66.9° had a slightly higher intensity than those of the spent catalyst in which also the graphitic carbon peak was detected [70] .…”
Section: Resultsmentioning
confidence: 92%
“…Nevertheless the peaks of the fresh catalyst are more intense than those of the spent catalyst and a new small peak of graphitic carbon appears on the spent material. [69,70] In the case of NiMo/Al the X-ray diffraction peaks of Ni (2θ = 44.5°and 51.8°) [71] and Mo (2θ = 40.5°and 50.7°) [72][73][74] species were not detected but small peaks of Ni at 2θ = 44.5°and Mo at 2θ = 40.5°were seen in the diffractogram of the fresh catalyst. γ-Al 2 O 3 peaks of the fresh catalyst at 2θ = 37.7°, 45.9°and 66.9°h ad a slightly higher intensity than those of the spent catalyst in which also the graphitic carbon peak was detected.…”
Section: Coke Depositionmentioning
confidence: 91%
“…Transition metals such as nickel- and cobalt-based catalysts have been proven to be very active and have widely been used for hydro processing in the heavy oil industry, as well as in the production of liquid biofuel [ 77 , 78 ]. Previous research showed that an alumina supported NiMo catalyst could be used to convert vegetable oil to alkanes and alkylbenzene [ 79 ]. In addition to that, alumina supported NiMo and CoMo catalysts are applicable as an effective deoxygenation catalyst to produce hydrocarbon products [ 80 ].…”
Section: Catalysis In Catalytic Pyrolysis Of Triglyceride Feedstocksmentioning
confidence: 99%